SIFAT FISIKO KIMIA DAN AKTIVITAS ANTIOKSIDAN MINYAK KELAPA MURNI (VCO) HASIL FERMENTASI RHIZOPUS ORIZAE - Dede Sukandar; Sandra Hermanto; Eva Silvia (Research Center for Chemistry - LIPI, 2009)
Research on physicochemical properties and antioxidant activity of VCO obtained from Rhizopus orizaefermentation had been done. Antioxidant activity was determined by DPPH method. Production of VCO had been carried out from coconut sample obtained from Pandeglang region with fermentation by Rhizopusorizae in variation of inoculum asfollow 2%, 5%, 7%, 10% and 12 %. Physicochemical test consist of density, refractive index, water content, free fatty acid, iodine value, peroxide value while the composition of fatty acid determined by GCMS, The result showed that variation of inoculum had significantly 0,024 influenced the yielded of VCO producted. Based on this result, quality of VCO still in the range of CODEX Standard, 19-1991rev.2-1999. It was found that antioxidant activity of VCO only 6.3% at 1000 ppm. The composition offatty acid based in lauric acid content measured by GCMS showed a significant result (49.48%-50%) agreed with COD EX Standard.Keyword: Antioxidant, DPPH, veo, Fermentation,Rhizopus oriza.